2012
DOI: 10.1007/s00421-012-2371-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat acclimation on endurance capacity and prolactin response to exercise in the heat

Abstract: We examined the effect of heat acclimation (HA) on endurance capacity and blood prolactin (PRL) response to moderate intensity exercise in the heat in young male subjects (n = 21). Three exercise tests (ET) were completed on a treadmill: H1 (walk at 60% VO(2)peak until exhaustion at 42°C), N (walk at 22°C; duration equal to H1) and H2 (walk until exhaustion at 42°C after a 10-day HA program). Heart rate (HR), skin (T (sk)) and core (T (c)) temperatures and body heat storage (HS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 36 publications
3
22
0
3
Order By: Relevance
“…These results are in agreement with our previous findings [20] that our subjects were acclimated through a 10-day exhaustive exercise program in the heat. As discussed earlier [20, 23] and in agreement with the findings of several studies [27, 43, 44], after the HA program, all our subjects showed improvement in EC, where the subjects' mean EC increased 86%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in agreement with our previous findings [20] that our subjects were acclimated through a 10-day exhaustive exercise program in the heat. As discussed earlier [20, 23] and in agreement with the findings of several studies [27, 43, 44], after the HA program, all our subjects showed improvement in EC, where the subjects' mean EC increased 86%.…”
Section: Discussionsupporting
confidence: 93%
“…The current investigation was a constituent part of a complex HA study [20, 23, 24]. To avoid natural HA, the study was conducted during the winter-spring period in Estonia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isothermic heat acclimation, where endogenous thermal stimulus is consistently targeted throughout, may positively sustain the rate of adaptation, or advance adaptation should a progressive increase in core temperature be implemented (Taylor and Cotter, 2006;Taylor, 2014). Progressive isothermic methods have only previously been implemented using models where the environmental conditions or workload for acclimation are increased (Burk et al, 2012;Chen et al, 2013;Daanen et al, 2011), this presumably to offset the aforementioned ongoing adaptation. These progressive methods are not certain to increase core temperature in the manner that a progressive increase in the isothermic target temperature would.…”
Section: Introductionmentioning
confidence: 98%
“…Physiological adaptations include lower resting core temperature, 4 lower core temperature and heart rate for a given exercise intensity, 5 and an earlier onset of sweating. 6 Collectively, such adaptations augment thermal tolerance of hot conditions to increase physical performance 7,8 and reduce the incidence of heat related illness.…”
mentioning
confidence: 99%